2021
DOI: 10.1016/j.imr.2020.100708
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen inhibition formula herbal mixture for danazol-induced precocious puberty in female rats: An experimental study with network pharmacology

Abstract: Background This study aimed at determining the effect of the herbal mixture estrogen inhibition formula (EIF) and its possible mechanisms by precocious puberty animal models and network pharmacology-based analysis. Methods Precocious puberty animal models were established by a single injection of 300 μg danazol, then female rats were administered EIF, vaginal openings were monitored, uterus and pituitary indices were determined. The levels of ALP, E2, LH, and FSH were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Our data showed that LH, FSH and E 2 were increased following leptin treatment as compared to the controls, which is consistent with the symptoms of PP, and the increases observed in other PP models (Park et al, 2021). However, after TAIII treatment, the levels of LH, FSH and E 2 in leptin-treated mice were decreased significantly, suggesting that TAIII is able to modulate the synthesis and/or secretion of these hormones, although the exact mechanisms of this modulation remain unclear.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data showed that LH, FSH and E 2 were increased following leptin treatment as compared to the controls, which is consistent with the symptoms of PP, and the increases observed in other PP models (Park et al, 2021). However, after TAIII treatment, the levels of LH, FSH and E 2 in leptin-treated mice were decreased significantly, suggesting that TAIII is able to modulate the synthesis and/or secretion of these hormones, although the exact mechanisms of this modulation remain unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Recent study shows that leptin communicates metabolic information with the brain neurons that control reproduction using GABAergic circuitry, resulting in releasing of GnRH from hypothalamic neurons (Burcelin et al, 2003) and puberty onset (Egan et al, 2017). In rats, the model of PP is established using da- nazol, a drug that can rapidly activate the HPGA leading to increased expression of KISS1 and GRP45 and onset of PP (Park et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Through this process, it was possible to confirm the need for a large-scale correlation study on various factors that can influence precocious puberty. In addition, Korea is a country where Western medical treatment for precocious puberty utilizing GnRH agonist and oriental medical treatment ( 32 ) utilizing herbal medicine to regulate hormones coexist. The majority of non-insured patients receiving oriental medical treatment are omitted from this study’s statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Precocious puberty refers to the onset of puberty characteristics (secondary sexual characteristics) before the age of 8 in girls and 10 in boys, including pseudoprecocious puberty, true precocious puberty, and incomplete precocious puberty (1). Idiopathic precocious puberty is more common in true precocious puberty, accounting for more than 80% of precocious puberty cases in girls, and mostly occurs at the age of 4-8 years (2).…”
Section: Introductionmentioning
confidence: 99%